Kearifan lokal dalam Kumpulan Cerita dari Kota 1001 Goa: kajian antropologi sastra - Damayanti, Rima; Fatimah, Khusnul; Bahrudin, Ahmad (Universitas Mulawarman, 2024)
The purpose of this research is to explore the values of local wisdom reflected in the stories, which include aspects of Pacitan community life such as religious system or religious ceremonies, community system, knowledge system, language, art, livelihood system, and tool system. The research method used is qualitative with a literary anthropology approach. The data were obtained through the data collection technique of listening and recording of quotations or sentences contained in the book “Kumpulan Cerita dari Kota 1001 Goa”. The analysis was carried out by dividing the data based on the identified local wisdom and then analyzing through description and interpretation of the research data. The results showed the existence of seven elements of local wisdom in the collection of stories, namely 9 data on religious systems and religious ceremonies, 3 data on community systems, 5 data on knowledge systems, 3 data on language, 4 data on art, 4 data on livelihood systems, and 8 data on tool systems. The existence of these seven elements is reflected in “Kumpulan Cerita dari Kota 1001 Goa” and can be revealed through an anthropology of literature approach.